The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s10508-022-02520-3
|View full text |Cite
|
Sign up to set email alerts
|

Does SARS-CoV-2 Affect Human Semen? A Systematic Review and Meta-Analysis

Abstract: Contradictory results have been reported regarding effects of the SARS-CoV-2 upon human semen. A timely and up-to-date systematic review with meta-analysis appears necessary. This study aimed to deliver pooled prevalence (PP) of SARS-CoV-2 in semen and pooled semen parameters as compared with the uninfected. The relevant databases were scanned by two authors for observational studies reporting analysis of semen in COVID-19 patients. The SARS-CoV-2-infected were assigned to group A (exposed arm), whereas the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on the published studies, we tend to conclude that SARS-CoV-2 has a negative impact on sperm parameters in the short term. This is supported not only by the “material basis” of SARS-CoV-2 infecting testicular cells through TMPRSS2 and ACE2 58 , but also by recent meta-analysis results 18 , 59 61 . Interestingly, there are discrepancies between case–control and self-controlled studies.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Based on the published studies, we tend to conclude that SARS-CoV-2 has a negative impact on sperm parameters in the short term. This is supported not only by the “material basis” of SARS-CoV-2 infecting testicular cells through TMPRSS2 and ACE2 58 , but also by recent meta-analysis results 18 , 59 61 . Interestingly, there are discrepancies between case–control and self-controlled studies.…”
Section: Discussionmentioning
confidence: 74%
“…Case–control studies show significant debates on the impact of SARS-CoV-2 infection on semen volume, sperm concentration, and sperm vitality, with half of the studies suggesting an impact and the other half indicating no effect. However, more studies suggest a decrease in total sperm count, with no significant effect on forward sperm movement 18 , 59 61 . In self-controlled studies, two meta-analyses 59 , 60 suggest a significant decrease in various sperm parameters after SARS-CoV-2 infection, aligning more with our current findings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a study compared semen samples from COVID-19-recovered males and those who had never had COVID-19, revealing lower sperm concentrations in the COVID-19 group, indicating potential adverse effects on male fertility, while sperm motility and morphology showed no significant differences between the groups [ 11 ]. A recent systematic review and meta-analysis show that even though the viral RNA is usually undetectable in semen, COVID-19 affects sperm concentration, total sperm count, and sperm volume [ 12 ]. However, some studies have shown that mild COVID-19 may have no detrimental effect on semen parameters [ 13 ], and there was no significant difference in spermiogram results between patients who presented for infertility before and during the COVID-19 pandemic [ 14 ], and even during the COVID-19 pandemic the sperm concentration, total sperm count, and total motility in male partners of infertile couples were better than those in the COVID-19 prepandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest reports even suggest a relationship between SARS-CoV-2 infection and the parameters of human semen. A 2023 meta-analysis found that sperm concentration, their total count per ejaculate, and semen volume were significantly reduced in virus-infected men compared to uninfected men [ 7 ].…”
Section: Introductionmentioning
confidence: 99%